Various Applications of Nonincisional Blepharoptosis Repair Technique in Secondary Surgeries. Issue 4 (June 2019) - Bae, Sangmo; Han, Jungkyu
Abstract : Abstract: Surgical correction of blepharoptosis is one of the most challenging procedures to oculoplastic surgeons. Based on our previous results in primary cases, we tried our nonincisional blepharoptosis correction technique in secondary operations. We mainly used our technique in reoperations with undercorrected ptosis, asymmetric eyelids, loosening of the supratarsal crease, and just for contour adjustments of eyelids. From March 2015 to August 2017, we performed the nonincisional blepharoptosis correction technique on total 93 patients in our clinic. We analyzed the results of the patients with after at least 6-month follow-up. Total 64 of 93 (69%) patients showed satisfactory results with non-ncisional technique. For the other 29 patients, we converted surgical method to the incisional approach during the operation. There was no major complication that required surgical intervention. Nonincisional blepharoptosis correction technique is a safe and reliable method, which can also be applied in secondary surgeries with proper indications.